1987
DOI: 10.1111/j.1471-4159.1987.tb09992.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Dopamine D1 and D2 Receptors in Nigral γ‐[3H]Aminobutyric Acid Release?

Abstract: This study examined the effects of dopamine D1 and D2 receptor agonists and antagonists on the spontaneous and calcium-dependent, K+-induced release of gamma-[3H]aminobutyric acid [( 3H]GABA) accumulated by slices of rat substantia nigra. SKF 38393 (D1 agonist) and dopamine (dual D1/D2 agonist) were without effect on [3H]GABA efflux by themselves (1-40 microM), or in the presence of the phosphodiesterase inhibitor isobutylmethylxanthine (IBMX) (0.5 mM), but potentiated evoked release in the presence of forskol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 50 publications
(57 reference statements)
1
35
0
1
Order By: Relevance
“…L-DOPA could stimulate D 1 receptors on striatonigral neurons (Gerfen et al, 1990), so to activate the "direct" pathway (Robertson and Robertson, 1989;Carta et al, 2005), or D 1 receptors on striatonigral nerve terminals (Starr, 1987;Aceves et al, 1991). The fact that TTX prevented the L-DOPA effect rules out this latter hypothesis, although it does not exclude an intranigral action of L-DOPA because this agent could stimulate GABAergic interneurons [dendritic location of D 1 receptors has been detected in the SNr (Huang et al, 1992)].…”
Section: Neurobiological Substrates Underlying J-113397/l-dopa Interamentioning
confidence: 89%
“…L-DOPA could stimulate D 1 receptors on striatonigral neurons (Gerfen et al, 1990), so to activate the "direct" pathway (Robertson and Robertson, 1989;Carta et al, 2005), or D 1 receptors on striatonigral nerve terminals (Starr, 1987;Aceves et al, 1991). The fact that TTX prevented the L-DOPA effect rules out this latter hypothesis, although it does not exclude an intranigral action of L-DOPA because this agent could stimulate GABAergic interneurons [dendritic location of D 1 receptors has been detected in the SNr (Huang et al, 1992)].…”
Section: Neurobiological Substrates Underlying J-113397/l-dopa Interamentioning
confidence: 89%
“…The increase in GABA release by D1 receptor stimulation in the VTA or substantia nigra (Starr, 1987;Timmerman et al, 1991;Cameron and Williams, 1994;Kalivas and Duffy, 1995) is blunted in rats pretreated with repeated injections of cocaine (Bonci and Williams, 1996). This poses the possibility that a D1-mediated reduction in inhibitory GABAergic tone may disinhibit glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rodents have suggested that D1LR antagonists may increase GABA levels in the SNr under some circumstances (Garcia et al 1997;Starr 1987), although this has not always been seen (Mayfield et al 1999). In our experiments, exposure to the D1LR antagonist increased the electrophysiologic activity of the majority of GPi cells and of a subset of SNr cells.…”
Section: D1lr Antagonist Effectsmentioning
confidence: 99%
“…Dopamine was shown to increase GABA release from rat brain slices in early studies (Reubi et al 1977), or to induce biphasic effects (van der Heyden et al 1980), perhaps explained by the fact that D1LR and D2LR receptors are activated by dopamine. Other studies of GABA release from brain slices showed that D1LR activation potentiates evoked GABA efflux in the SNr (Aceves et al 1995;Floran et al 1990;Starr 1987), although this was not true in other studies (Mayfield et al 1999). Published reports on the effects of D1LR activation on GABA release in vivo, studied in awake rats with microdialysis techniques, have consistently demonstrated that D1LR activation increases GABA levels in the SNr (Matuszewich and Yamamoto 1999;Rosales et al 1997;Timmerman and Westerink 1995;Trevitt et al 2002;You et al 1994) and entopeduncular nucleus (the rodent homologue of the primate GPi; Ferre et al 1996).…”
Section: D1lr Agonist Effectsmentioning
confidence: 99%